Utilization and Management Model of Pelagic Fish Resources - Damayanti, Herna Octivia (Universitas Negeri Semarang, 2018)
Pelagic fish was the main raw material for fish processing industry. Rate of fishing that not equivalent with the growth of fish resources, eventually will decrease the catch of fishermen. Aims of the research were (1) to estimate the bioeconomic of pelagic fish resources on MSY (Maximum Sustainable Yield), MEY (Maximum Economic Yield) and OA (open Access) conditions; (2) to estimate the optimum utilization rate, (3) arrange the management model of sustainability pelagic fish resources in Pati regency. This research was descriptive quantitative and conducted in March until September 2017. Reseacrh location in Bajomulyo village and Bendar village Juwana Subdistrict with 35 samples. Data analysis : (1) gear standardization, (2) bioeconomic static optimation model approach, (3) bioeconomic dinamic optimation model approach, (4) reconstruction of in-depth interview results. Result of the research are (1) bioeconomic static optimation model approach namely, biomass MEY>MSY>OA, catch MSY>MEY>OA, effort OA>MSY>MEY, profit MEY>MSY>OA; (2) bioeconomic dinamic optimation model approach namely, biomass MEY>MSY>OSY>OA, catch MSY>MEY>OSY>OA, effort OA>MSY>OSY>MEY, profit MEY>>OSY>MSY>OA; (3) pelagic fish management model are input controlling, output controlling and technical provisions.